2004
DOI: 10.1007/s00018-003-3406-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the design of inhibitors of aldose reductase, an enzyme showing pronounced induced-fit adaptations

Abstract: Aldose reductase is involved in the polyol pathway, catalyzing the reduction of glucose to sorbitol. However, due to pronounced binding site adaptations, the enzyme can operate on a broad palette of structurally diverse substrates ranging from small aliphatic and aromatic aldehydes up to steroid-type ligands. A comparative analysis of the presently accessible crystal structures of aldose reductase complexes reveals four binding-competent protein conformations. Additional relevant conformers are detected throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
0
29
1
4
Order By: Relevance
“…Results clearly showed that introduction of a substituted pyrazole ring on 2H-pyridazin-3-one and 6-chloropyridazine led to a marked decrease in AR inhibitory potency. This finding is in contrast to many effective AR inhibitory compounds possessing ring systems similar to that of pyrazole such as thiazole (Klebe et al, 2004;Maccari et al, 2005), oxadiazole (Klebe et al, 2004), pyrolidine (Pau et al, 2004), hydantoin, and related cyclic imides (Buyukbingol et al, 1994) (Fig. 2).…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Results clearly showed that introduction of a substituted pyrazole ring on 2H-pyridazin-3-one and 6-chloropyridazine led to a marked decrease in AR inhibitory potency. This finding is in contrast to many effective AR inhibitory compounds possessing ring systems similar to that of pyrazole such as thiazole (Klebe et al, 2004;Maccari et al, 2005), oxadiazole (Klebe et al, 2004), pyrolidine (Pau et al, 2004), hydantoin, and related cyclic imides (Buyukbingol et al, 1994) (Fig. 2).…”
Section: Resultscontrasting
confidence: 45%
“…1). In situations of increased glucose flux, sorbitol can accumulate in cells of insulin-dependent glucose uptake, leading to increased osmotic pressure in the cells (Klebe et al, 2004). The pathophysiological activity of AR plays a key role in the development of degenerative long-term diabetic complications such as neuropathy, nephropathy, retinopathy, cardiomyopathy, and cataract formation (Suzen and Buyukbingol, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The active site of AKR1B1 consists of two major pockets, the so-called “anionic” pocket and the “specificity” pocket [30]. The active site of AKR1B1 can accommodate a multitude of substrates due to the flexibility of the “specificity pocket” residues [31].…”
Section: Resultsmentioning
confidence: 99%
“…However, as shown for h3α-HSD3, certain residues of the steroid-binding site can undergo significant conformational changes dictated, in part, by the shape of the steroid itself, changes that are essential for the correct orientation of the steroid and for the position and stereospecificity of the oxydo-reduction reaction. 14 This binding site adaptation, similar to the "ligand induced-fit mechanism" reported for the aldose reductase, 16 is of major importance for the steroid-binding specificity and is very difficult to predict without determining the crystal structure of these enzymes in complex with their substrates.…”
Section: Introductionmentioning
confidence: 82%